A CASE STUDY ON THE AWARENESS OF BREAST AND ORAL CANCERS AMONG THE STUDENTS IN SHANTHI NAGAR, BENGALURU, KARNATAKA - Saniya K Ramesh (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Breast cancer and oral cancer are among the most prevalent types of cancer affecting women in India. Nevertheless, the knowledge among the population about these diseases is inadequate. An online questionnaire survey was conducted from 25th May, 2022 to 15th June, 2022 in a sample of 50 consenting students in Shanthi Nagar, Bengaluru. The questionnaire was self-administered so as to avoid biassed responses. Apart from their socio-demographic characteristics, the participants were asked to answer 30 questions to assess their proficiency in breast and oral cancer. The volunteer sample exhibited satisfactory knowledge of these cancers. The mean total score based on their understanding of the diseases is 58.5%. However, 78.6% of the students do not know the steps of breast self-examination whereas 88.1% do not know that of oral cancer. Over 64% of the respondents have never done self-examination for cancer in their lifetime. The frequency of self-examination practices among the students of Shanthi Nagar is negligible. This is indicative of the lack of awareness programs among the population. It is highly suggested that campaigns be organised to educate the people on the gravity of early diagnosis and self-examination.